Surveillance for Mosquito-borne Viruses - C. Roxanne Rutledge-Connelly (EDIS, 2004)
There are three very important mosquito-borne diseases that occur in Florida: Eastern equine encephalitis, St. Louis encephalitis, and West Nile fever/encephalitis; all of these diseases are caused by viruses that are transmitted by the bite of an infected mosquito. This document considers the monitoring of virus activity, that is, surveillance for the organisms which mosquitoes can transmit from one host (e.g. bird) to another (e.g. human). This document is Fact Sheet ENY-699 one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Date first published: March 2004.